PENERAPAN METODE PENCATATAN DAN PENILAIAN PERSEDIAAN BARANG MENURUT SAK ETAP PADA CV. TJIPTO PUTRA MANDIRI INDONESIA - Herwin Budianto; Dian Ferriswara (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2017)
The inventory problem is a problem always faced by decision makers in the production process, inventory recording is done to ensure the certainty that when needed these items are available.Companies engaged in trading and services need to make accounting records to determine the financial condition of the business.The need for accounting information of merchandise inventory is a very important part related to the inventory of merchandise. Due to the most frequent activity in order to achieve business smoothness. Accounting for merchandise inventory requires an inventory card which includes purchase invoices, sales invoices, proof of incoming goods, or outgoing goods relating to inventory. A good accounting system that is assessment of inventory will be a means to provide information that can be used in the evaluation of the company as well as a tool for good internal control. Companies are required to be able to apply the company's accounting policy well in order to provide accurate information for the smooth activity of the company. Therefore, the company must follow the Financial Accounting Standards (SAK), precisely the Financial Accounting Standards Entity Without Public Accountability (SAK ETAP) formulated by the Indonesian Institute of Accountants (IAI) in 2009. The purpose of this study is to describe the determination of method of recording and valuation of goods inventory according to SAK ETAP applicable in Indonesia. The method used in this study is with a qualitative approach, the type of case study research, where the study was conducted on the company engaged in automotive retailing which has business activities trading, as a provider of various types of merchandise that sells the needs of spare parts four-wheeled vehicles and two wheels.The main activity is to buy merchandise to suppliers for resale to consumers without having to change the form of goods in order to gain profit. The inventory valuation method used in the FIFO (first in first out) / MPKP assessment method (first entry first exit). This method is used so as not to stock up on merchandise for too long so that the goods sold are worth selling goods. This method is in conformity with the Financial Accounting Standards of an Entity Without Public Accountability regarding inventory.The existence of information technology system (STI) so far is very helpful and simplify the process of recording and valuation of merchandise inventory on the CV. Tjipto Putra Mandiri Indonesia as well as the development of record keeping information system, hoping to be better systematically, effectively efficient and minimize any recording errors.